2022
DOI: 10.1155/2022/9621764
|View full text |Cite|
|
Sign up to set email alerts
|

Role of miR-498 Combined with CREB1 in Apoptosis and Invasion of Hepatoma Cell Line

Abstract: Objective. To detect the expression levels of miR-498 in the hepatoma cells and to clarify the biological roles of miR-498 in hepatoma by investigating CREB1, which is the target of miR-498. This study provides a new biomarker for the early diagnosis and targeted therapies for hepatoma. Methods. The expression of miR-498 between hepatoma cells and hepatocytes was detected by qRT-PCR. miR-498 was overexpressed in hepatoma cells, and then, flow cytometry was used to analyze the cell apoptosis rate. Cell migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%